(3CQLhRI aj GdWHs - (3SYjO Hf YHO GdQMef Hf eMeO Hf YHO QHg, CHh YKeGf,J (B340 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HQGfG hQcH GdYbhd hGdCPgGfG s
(3BNQgG (B:s
(3hWGgQ ai GdcYH GdQOQbi YQb jcfi HGdfSG eMbb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs